Building Information Modeling (BIM) in Malaysian construction industry: benefits and future challenges - Musa, Suria; Marshall-Ponting, Amanda; Abdul Nifa, Faizatul Akmar; Shahron, Syairah Aimi (IP Publishing LLC, 2018)
Building Information Modeling is an innovative technology coupled with process and human interactions.BIM has been used by the Architecture, Engineering, and Construction (AEC) industry in developed and developing countries including Malaysia.The reason for having BIM in practice triggered by the Director of Public Works Department (PWD) in 2009; who urged construction companies to adopt ICT to enhance productivity and efficiency. This paper aims to explore the BIM implementation in Malaysian Construction Industry. A literature review was carried out to explore on existing BIM implementation that includes definitions, BIM applications, BIM benefits and BIM future challenges.The data collected from various sources such as books, journal articles, conference papers and material available on the Internet, which related to BIM. The review highlights on several BIM benefits regarding financial, better information, communication and coordination, respond to complexity, improved visual, improved sustainability, improved safety and also create service’s or business’s opportunities.Nevertheless, implementing BIM is not without challenges although it gains attention from many countries. Some issues regarding culture, technology, process and policy for the construction stakeholders, organizations and policymaker have been raised to take up the challenges for effective BIM implementation.